A Review and Proposed Rationale for the use of Ultrasonography as a Diagnostic Modality in the Identification of Bone Stress Injuries. (14th April 2018) - Fukushima, Yaeko; Ray, Jeremiah; Kraus, Emily; Syrop, Isaac P.; Fredericson, Michael
Abstract : Bone stress injuries are common in military personnel and athletes. The delayed diagnosis of a bone stress injury can lead to a more severe injury that requires a longer period of treatment. The early detection of bone stress injuries is a central part of management. Currently, the reference standard for detecting bone stress injuries is magnetic resonance imaging. However, the expanding use of point‐of‐care ultrasonography (US) may enable the early detection of bone stress injuries in the clinical setting. In this article, we review the US detection of bone stress injuries, as well as discuss the rationale for the use of US in the diagnosis of these injuries.